Melting Experiments on Liquidus Phase Relations in the Fe‐S‐O Ternary System Under Core Pressures. Issue 10 (16th May 2019) - Yokoo, Shunpei; Hirose, Kei; Sinmyo, Ryosuke; Tagawa, Shoh
Abstract: Melting experiments on the Fe‐S‐O ternary system were performed to 208 GPa in a laser‐heated diamond‐anvil cell. Compositions of liquids and coexisting solids in recovered samples were examined using a field‐emission‐type electron microprobe. The results demonstrate that the ternary eutectic point shifts toward the oxygen‐rich, sulfur‐poor side with increasing pressure, in accordance with changes in eutectic liquid compositions in the Fe‐O and Fe‐S binary systems. We also found that solid Fe crystallizing from liquid Fe‐S‐O does not include oxygen, while the partitioning of sulfur into solid Fe is enhanced with increasing pressure. These indicate that oxygen‐rich, sulfur‐poor liquid crystallizes Fe at the inner core boundary; however, it makes a large density difference between the liquid and solid core, which is inconsistent with observations. Alternatively, we found that a range of C‐bearing, S‐poor/O‐rich liquids account for the density and velocity in the outer core and the density in the inner core. Plain Language Summary: Light elements in the Earth's core have not been identified yet. The core composition is constrained by the liquidus phase relations of iron alloyed with light elements at high pressure, because the outer core is crystallizing Fe that is depleted in light elements at the inner core boundary. The liquidus phase relations in ternary systems are sometimes different from those of binary systems but have been examined little under core pressures. Sulfur and oxygen have been considered important light elements in the core. Here we performed melting experiments on Fe‐S‐O ternary alloys up to 208 GPa using a laser‐heated diamond‐anvil cell and determined the liquidus phase relations on the basis of textural/chemical characterizations of recovered samples. We also found that the partitioning of sulfur causes a small density contrast between coexisting solid and liquid, but oxygen makes a large difference. These results demonstrate that O‐rich, S‐poor liquid iron crystallizes Fe but causes a liquid/solid density contrast much larger than what is observed across the inner core boundary, suggesting that other light elements are required. Alternatively, we searched for possible liquid core compositions in Fe‐S‐O‐Si and Fe‐S‐O‐C and found a range of liquids in the latter system are compatible with seismological observations. Key Points: Liquidus phase relations in the Fe‐S‐O ternary system were obtained by melting experiments up to 208 GPa O‐rich, S‐poor liquid iron alloy crystallizes solid Fe at the ICB The outer core can be a C‐bearing, O‐rich/S‐poor liquid that is compatible with seismological observations